Heat Shock Proteins: Cell Protection through Protein Triage - David Lanneau; Guillaume Wettstein; Philippe Bonniaud; Carmen Garrido (The Scientific World Journal)
Heat shock proteins (HSPs) are chaperones that catalyze the proper folding of nascent proteins and the refolding of denatured proteins. The ubiquitin-proteasome system is an error-checking system that directs improperly folded proteins for destruction. A coordinated interaction between the HSPs (renaturation) and the proteasome (degradation) must exist to assure protein quality control mechanisms. Although it still remains unknown how the decision of folding vs. degradation is taken, many pieces of evidence demonstrate that HSPs interact directly or indirectly with the proteasome, assuring quite selectively the proteasomal degradation of certain proteins under stress conditions. In this review, we will describe the different data that demonstrate a role for HSP90, HSP70, HSP27, and alpha-B-crystallin in the partitioning of proteins to either one of these pathways, referred as protein triage.